Low-Cycle Fatigue Life Prediction of 10CrNi3MoV Steel and Undermatched Welds by Damage Mechanics Approach - Song, W.; Liu, X.; Xu, Jie; Fan, Yu; Shi, Duanhu; Yang, Feng; Xia, Xiaolei; Berto, F.; Wan, Di (Frontiers in Materials, 2021)
Welding of steel is a technique frequently used in practical engineering applications, however, their mechanical performance is strongly dependent on the physical metallurgical status of the weldments. In the present study, fully-reversed, strain-controlled Low Cycle Fatigue (LCF) tests were conducted on 10CrNi3MoV steel and its under-matched weldments with strain amplitudes varying from Δε=±0.5% to ±1.2%. Both base metal and weldments exhibited softening behavior at the beginning of the cyclic stage. Numerical investigations of cyclic stress-strain evolutions of the materials have been studied by the cyclic plastic model considering nonlinear hardening. The Continuous Damage Mechanics (CDM) theory based on the experimental hysteresis stress-strain energy concept was employed to illustrate LCF fatigue failure, including damage initiation and deterioration. The damage mechanics approach calibrates the material parameters from the measured fatigue life for initiation and growth stages. Afterwards, the combination of material cyclic plastic parameters and damage parameters was implemented to predict the LCF life. Good agreement can be observed between the experimental results and the FE results based on the CDM approach. Finally, the damage evolution of the materials under different strain amplitudes by this approach was assessed.